2015
DOI: 10.1097/npt.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Neurorehabilitation Strategies Focusing on Ankle Control Improve Mobility and Posture in Persons With Multiple Sclerosis

Abstract: The outcomes of this exploratory study suggest that the neurorehabilitation protocol employed in this investigation has the potential to promote clinically relevant improvements in the ankle plantarflexor control, standing postural balance, ankle plantarflexion strength, and the mobility of individuals with MS. Video abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A110).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
2
12
1
Order By: Relevance
“…Our behavioral results show that individuals with MS have impairments in the precision of the lower extremity force production, which is consistent with our previous work [Arpin et al, ; Davies et al, ]. Specifically, we found that individuals with MS had slower reaction times and a greater amount of overshoot of the presented targets.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our behavioral results show that individuals with MS have impairments in the precision of the lower extremity force production, which is consistent with our previous work [Arpin et al, ; Davies et al, ]. Specifically, we found that individuals with MS had slower reaction times and a greater amount of overshoot of the presented targets.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple sclerosis (MS) is a demyelinating disease that impacts the function of the central nervous system, and often results in impaired muscular performance. Previously, we have shown that individuals with MS have greater errors when attempting to control the precision of the lower extremity force production [Arpin et al, ; Davies et al, ]. While these results are insightful, the neurophysiological abnormalities that may be responsible for the reduced muscular force control remains unknown.…”
Section: Introductionmentioning
confidence: 88%
“…Prior investigations have shown that a greater amount of variability in a submaximal continuous isometric contraction performed with the ankle plantarflexors is related to decreases instanding postural stability (Kouzaki & Shinohara, 2010;Mello, Magalhaes, & Kohn, 2013). Additionally, in our previous investigation, we displayed that a heightened amount of variability in the continuous isometric ankle plantarflexorforce productionwas related withthe degree of upright postural balance impairments seen in individuals with MS (Davies, et al, 2015).Furthermore, a reduction in the amount of variability in the isometric plantarflexion force production seen afterindividuals with MS undergo physical therapywas related to the degree of improvements seen in their standing postural control. However, the reduction in the variability of the continuous isometric plantarflexion force productionwas not related to the improvements in walking ability.…”
Section: Introductionmentioning
confidence: 53%
“…The restoration of an efficient ankle push-off has previously been reported and associated with the reduction of a compensatory movement strategy. 11,22 In our case study, the underlying mechanism may be related to the improvement in ankle kinematics, by restoring a heel strike at initial contact and increasing the plantarflexion during preswing. The quality of gait was also improved with a better gait symmetry illustrated by a similar step length of both the paretic and nonparetic sides, as has been reported by others.…”
Section: Discussionmentioning
confidence: 95%